Prevalence of diabetes and presence of autoantibodies against zinc transporter 8 and glutamic decarboxylase at diagnosis and at follow up of Graves’ disease - Jonsdottir, Berglind; Jönsson, Ida; Lantz, Mikael (Endocrine, 2019)
Purpose The aim of this work was to investigate, in patients with newly diagnosed Graves’ disease (GD), the frequency of islet autoantibodies including autoantibodies against Zink transporter 8 (ZnT8A), as well as to investigate the relation between thyroid autoantibodies, islet autoantibodies and diabetes both before GD diagnosis and at follow-up. Methods Blood samples from 278 patients with newly diagnosed GD were analyzed for autoantibodies against glutamic acid decarboxylase (GADA), insulinoma-associated protein-2 (IA2-A), three variants of zinc transporter 8 (ZnT8A), thyroid peroxidase (TPOA) and the TSH receptor (TRAb). Information on other autoimmune diseases, as well as development of diabetes during follow up was gathered from patient’s medical journal. Results At GD diagnosis, 13.7% were positive for islet autoantibodies, with the majority being positive for GADA (8.7%) and ZnT8A (7.6%). TPOA were found positive in 71% and TRAb in 83%. No association was found between islet autoantibodies and thyroid autoantibodies or diabetes diagnosis during follow up. Positive association was found between islet autoantibodies and all forms of diabetes, diagnosed both before and after GD (OR: 2.5, CI: 1.1–6.8, p = 0.03) but not to other autoimmune diseases at GD diagnosis. Conclusions The incidence of GADA and ZnT8A in patients with GD is high and might indicate wide range endocrine autoimmunity, as well as risk for non-autoimmune diabetes rather than exclusively mark beta cell autoimmunity and type 1 diabetes.